THE MISUSE OF ICT BY STUDENTS: THE EFFECTS OF PHORNOGRAPHY AND THE TEACHER SOLUTIONS - Eka Apriani (Tadrib: Jurnal Pendidikan Agama Islam, 2015)
ICT is information and communication technology. These technology are telephony, CD ROM, audio or video clips, radio, television, broadcasting, computer, and internet. The most common technology used by people is computer and internet. Internet has an important role in our life. We can find everything using an internet connection. The internet has two effects for students: positive and negative. This paper only focuses on negative effects because it is very dangerous. One of the negative effects using internets is pornography. Pornography is very dangerous for students since it can decrease students’ morality. For this condition, teachers become an important person who have significant roles in avoiding the pornography affects the students. The  teachers have authority to control and monitors students’ activity, at least at school, where students spend most of their time. One of effective ways to avoid pornography is through giving a sex education to the students in which they will get information about what are they have to do and not.